2011
DOI: 10.1007/s10336-011-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Does niche-overlap facilitate mixed-species flocking in birds?

Abstract: Foraging niche overlap between attendant species and the nuclear species of mixed-species flocks may induce competition as well as facilitation. In this study, we hypothesized that canopy species would appear more frequently in flocks where nuclear species foraged in the canopy and that species with greater niche overlap with nuclear species would have lower departure rates. Flocking and foraging behaviors of flocks led by the Grey-cheeked Fulvetta Alcippe morrisonia were studied in northeastern Taiwan for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…nigriceps . The hypothesis that vertical distribution is a determinant of bird species assemblage was suggested by [ 52 ] and has been widely tested [ 53 55 ]. The findings of the present study provide further support that vertical distribution is important in niche partitioning of bird species and probably led to sympatric babbler species assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…nigriceps . The hypothesis that vertical distribution is a determinant of bird species assemblage was suggested by [ 52 ] and has been widely tested [ 53 55 ]. The findings of the present study provide further support that vertical distribution is important in niche partitioning of bird species and probably led to sympatric babbler species assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…In most tropical forests, a significant percentage of the birds are found participating in flocks at any one time [41], with an average of 48% of individuals found in flocks in our region [33]. Mixed-species flocking can increase foraging efficiency (reviewed by Sridhar et al [6]), through social copying [49,50] and the use of other species as beaters by some fly-catching species [51]. Such flocking can also decrease predation risk through a variety of mechanisms, including risk dilution and alarm calling [7,41,52].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, especially on tit-led temperate systems, have shown that tits may change where they feed in trees (Morse 1970;Alatalo 1981;Alatalo et al 1985Alatalo et al , 1987Krams 2001;Jabłoński and Lee 2002) or their foraging technique (Pomara et al 2003) to avoid dominant species in flocks. At the same time, however, other studies have demonstrated that species might actually move their foraging location to be close to other species, particularly leaders (Latta and Wunderle 1996;Hino 1998;Hsieh and Chen 2011;Farine and Milburn 2013), and sallying species adjust their location to capture insects disturbed by gleaners (Satischandra et al 2007;Srinivasan and Quader 2012;Sridhar and Shanker 2014). Valburg (1992) described a primarily frugivorous species that was insectivorous in flocks.…”
Section: Reviewmentioning
confidence: 99%
“…This gregariousness makes them conspicuous in flocks, and the possibly kin-selected signals they use for intraspecific communication, especially those related to predation threats, can be eavesdropped on by other species Harrison and Whitehouse 2011). Nuclear species also tend to be generalists that range over a wide variety of foraging heights, and leaf-gleaning species that disturb insects as they move, making them attractive to follow for a wide-range of other species (Hino 1998;Hsieh and Chen 2011).…”
Section: Explaining Patterns In Flock Organization and Leadershipmentioning
confidence: 99%